On teaching fundamentals of calculus at secondary school - Apynis, Antanas (Lietuvos matematikos rinkinys, 2010)
The article, from different didactical aspects, analysis the problem of teaching fundamentals of calculus at secondary school. Continuity and limit of a function are suggested to be explained on the base of an informal concept and examples of these notions. An explanation of this kind is completely sufficient in solving problems of calculation of limits and derivatives of rational functions as well as other problems.